Entrepreneurial leadership and employees' proactive behaviour: Fortifying self determination theory - Muhammad Bilal; Shafaq Chaudhry; Hina Amber; Muhammad Shahid; Shoaib Aslam; Khuram Shahzad (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The prevailing pandemic (COVID-19) has increased socioeconomic problems and caused psychological distress due to work uncertainty, specifically in emerging economies. Small and medium enterprises (SMEs) in emerging economies have been severely affected. Particularly, work uncertainty is becoming a hindrance towards proactive work behaviour (PWB) that can be improved by an effective entrepreneurial leadership role and proactive personality attribute. Based on fortifying self-determination theory, this research answered the question to what extent proactive personality moderates the relationship between work uncertainty and PWB and strengthens the relationship between entrepreneurial leadership and PWB. To empirically examine the study's underlying theoretical framework, respondents were selected from SMEs working in Pakistan from the high-tech industry. Multisource data were accumulated from 420 workers and their leaders utilizing a two-wave, time-lagged research design. Conclusions revealed that entrepreneurial leadership first reduced individuals' work uncertainty, which in turn, led to enhanced proactive work behaviour of employees. Furthermore, the results revealed that work uncertainty mediates the relationship between entrepreneurial leadership and proactive work behaviour. Moreover, proactive personality moderates the link concerning work uncertainty and proactive work behaviour, such that this association is significant only when proactive personality is low. Additionally, the moderated mediation analysis indicated that less proactive people, compared with their extraordinarily proactive colleagues, trusted entrepreneurial leadership to be more proactive in the workplace. These findings have important implications to induce PWB among employees.
Keywords: 650; entrepreneurial leadership; work uncertainty; proactive work behaviour; proactivepersonality; innovation; self-determination theory